2007
DOI: 10.1108/17511870710745439
|View full text |Cite
|
Sign up to set email alerts
|

Linking learning methods to outcomes in public health leadership development

Abstract: This is the first published evaluation that has attempted to link specific learning methods with outcomes for participants of a public health leadership development program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…These points are all in keeping with the findings of other health care leadership studies (see e.g. Block & Manning, 2007;Miller et al, 2007). Miller et al found specific evidence that support programs, consisting of coaching and mentoring, and team-based work assignments post-training were particularly helpful in solidifying leader learning and in developing important social support networks.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…These points are all in keeping with the findings of other health care leadership studies (see e.g. Block & Manning, 2007;Miller et al, 2007). Miller et al found specific evidence that support programs, consisting of coaching and mentoring, and team-based work assignments post-training were particularly helpful in solidifying leader learning and in developing important social support networks.…”
Section: Discussionsupporting
confidence: 65%
“…Since the majority of these trainees said they had also acted actively worked on applying their goals, this training program content had been reinforced with practice and thus more likely to be easily accessible. This finding seems to provide support for the need for ongoing reinforcement of the content to help trainees apply their goals in their daily activities and to make those lasting linkages with the program content (Block & Manning, 2007;Miller, et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Particular instructional methods, such as selfassessment tools, action learning and case discussions, can result in particular leader outcomes, like changed understanding, increased confi dence and self-awareness and changes to clinical leadership practice (Miller, Umble, Dinkin, & Frederick, 2007). Nevertheless, despite instructional methods giving rise to specifi c outcomes, participants frequently integrate information and skills from multiple methods to achieve particular outcomes (Miller et al, 2007).…”
Section: Individual-level Outcomes From a National Clinical Leadershimentioning
confidence: 98%
“…In health care, multiple-source feedback, an important component of the ILDP, has been shown to improve physicians' communication with their patients, families and colleagues, increase self-reflection, strengthen intention to improve areas of professional practice, and change behavior in interactions with peers (Miller, Umble, Frederick, & Dinkin, 2007).…”
Section: Attitudes and Beliefsmentioning
confidence: 99%